(untitled) (Bangladesh Journal of Animal Science, 2024)
This study was aimed to assess the potential of using milk’s nitrogen distribution pattern, specifically casein, whey protein, and non-protein nitrogen content, as a method for detecting milk adulteration with water, sugar, and flour. Whole milk samples were collected from the Bangladesh Agricultural University Dairy Farm, BAU, Mymensingh, and subjected to adulterations, including 15%, 20%, and 25% water additions and subsequent sugar or flour adjustments to match the fresh milk’s specific gravity. The samples were analyzed for specific gravity, fat content, and nitrogen distribution. Results indicated that while specific gravity remained consistent across samples adulterated with sugar or flour, it varied significantly (P<0.05) in those diluted with water. Fat content was significantly (P<0.05) reduced in samples adulterated with water and sugar, particularly at the 25% water addition level. Though total protein, true protein, and casein contents were significantly lower (P<0.05) in the 25% water-added milk compared to fresh milk, they were not significantly different (P>0.05) across the other adulterated samples when compared to fresh milk. Whey protein and non-protein nitrogen levels were statistically consistent (P>0.05) across all the samples. The results indicate that the nitrogen distribution pattern, in its current state, cannot be used to detect milk adulteration effectively. Further research with a larger dataset considering various factors affecting nitrogen distribution in milk is recommended for conclusive results. Bangladesh Journal of Animal Science 53 (1): 23-30, 2024